2007
DOI: 10.1016/j.ultrasmedbio.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Induced Thermal Elevation in Clotted Blood and Cranial Bone

Abstract: Ultrasound thermal effects have been hypothesized to contribute to ultrasound-assisted thrombolysis. To explore the thermal mechanism of ultrasound-enhanced thrombolysis with recombinant tissue plasminogen activator (rt-PA) for the treatment of ischemic stroke, a detailed investigation is needed of the heating produced in skull, brain and blood clots. A theoretical model is developed to provide an estimate for the worst-case scenario of the temperature increase in blood clots and on the surface of cranial bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…However, several studies have shown negligible thermal effects in bench-top (Francis et al 1992; Shaw et al 2006; Damianou et al 2014) or clinical studies (Barlinn and Alexandrov 2013). Numerical computations confirm a negligible temperature rise in clots due to 0.12–3.5 MHz insonations during thrombolysis (Nahirnyak et al 2007; Bouchoux et al 2014). In contrast, Sakharov et al (2000) attributed increased thrombolytic efficacy from 1-MHz insonation in-vitro due to the combined effect of heating and acoustic streaming.…”
Section: 2 Mechanisms Of Thrombolytic Enhancementmentioning
confidence: 78%
“…However, several studies have shown negligible thermal effects in bench-top (Francis et al 1992; Shaw et al 2006; Damianou et al 2014) or clinical studies (Barlinn and Alexandrov 2013). Numerical computations confirm a negligible temperature rise in clots due to 0.12–3.5 MHz insonations during thrombolysis (Nahirnyak et al 2007; Bouchoux et al 2014). In contrast, Sakharov et al (2000) attributed increased thrombolytic efficacy from 1-MHz insonation in-vitro due to the combined effect of heating and acoustic streaming.…”
Section: 2 Mechanisms Of Thrombolytic Enhancementmentioning
confidence: 78%
“…The largest temperature increase in brain tissue was located next to the insonified bone and was slightly lower than the temperature increase in periosteal tissue. Correspondingly, a slight difference of temperature between the two opposite interfaces of the insonified bone was measured in vitro by Nahirnyak et al (2007).…”
Section: Discussionmentioning
confidence: 93%
“…Nahirnyak et al (2007) measured in vitro a temperature increase of 0.6°C on the surface of temporal bone exposed to 120-kHz ultrasound with a 0.25 MPa peak-to-peak pressure in the free field and an 80% duty cycle. To compare their in vitro measurement with the values of Δ T max obtained by simulation in patient heads (Table 3), the equivalent temporal-average acoustic intensity in the M1 segment must be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In contrast to high-intensity continuous ultrasound, LIPUS (<100 mW/cm 2 ) has much lower intensities, which are regarded as nonthermogenic and nondestructive. 20 Mechanical strains received by cells may result in biochemical events and increase membrane permeability.…”
Section: Discussionmentioning
confidence: 99%